2010
DOI: 10.1007/dcr.06013e3181c7525c
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bladder Catheter Drainage Following Pelvic Surgery—Is It Necessary for That Long?

Abstract: Routine prolonged urinary bladder catheterization after pelvic surgery may not be required, and the Foley catheter may be safely removed on postoperative day 1. Larger studies are needed to confirm the findings of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 20 publications
0
63
1
1
Order By: Relevance
“…Accordingly, Medicare and Medicaid have discontinued reimbursement for the care of UTI in the postoperative setting, labeling them a potentially preventable condition. While this has put additional pressure for quicker removal of catheters, early (within 48 h after surgery) removal of urinary catheters has been associated with increased rates of urinary retention (UR) [4][5][6][7][8][9]. Reported rates of UR after pelvic surgery have been between 5 and 22 %, higher than those reported after upper abdominal surgery.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, Medicare and Medicaid have discontinued reimbursement for the care of UTI in the postoperative setting, labeling them a potentially preventable condition. While this has put additional pressure for quicker removal of catheters, early (within 48 h after surgery) removal of urinary catheters has been associated with increased rates of urinary retention (UR) [4][5][6][7][8][9]. Reported rates of UR after pelvic surgery have been between 5 and 22 %, higher than those reported after upper abdominal surgery.…”
Section: Introductionmentioning
confidence: 97%
“…Multiple factors have been associated with an increased risk of UR including age, duration of surgery, type of surgery, and level of anastomosis in the pelvis [2,5,8,9]. In particular, reported rates of UR are higher in men than in women [6][7][8][9]. The increased incidence of UR in pelvic surgery is likely multifactorial resulting from prolonged operative times in pelvic surgery (and thus higher fluid intake), prostatism and potential damage to pelvic nerves [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The articles comprising this subject area are about the length of time the catheter remains in situ and its removal, use of a fixation device and the procedure of clamping of the closed system and its relation to reduction of UTI ( In surgical patients, the removal of the indwelling catheter in the first day post-surgery, compared to removal on the fourth or fifth day postoperative was associated with a lower incidence of UTI, although there was an increased risk of re-catheterization (30)(31)(32)(33)(34)(35)(36) .…”
Section: Maintenance and Removal Of The Cathetermentioning
confidence: 99%
“…It is recommended that catheter remain in place after surgery for up to 24 hours, to reduce rates of symptomatic UTI (30)(31)(32)(33)(35)(36)(37) . It is suggested that the early removal of the catheter, on the other hand, during the night in comparison to the morning, decreases the patient's stay in hospital, saving resources (37) .…”
Section: Studies Were Not Found In This Irmentioning
confidence: 99%
“…The current literature suggests that urinary catheters can be safely removed 1-2 days after a colorectal resection, even with a thoracic epidural in place. 10,11 The current shift to "fast-track surgery" includes the early removal of urinary catheters, which has reduced the rate of UTIs from 24% to 4%. 12 One might also question whether the benefits of routine prophylaxis outweigh the harms.…”
Section: Formation Médicale Continuementioning
confidence: 99%